2005
DOI: 10.1002/yd.111
|View full text |Cite
|
Sign up to set email alerts
|

Activities, engagement, and emotion in after‐school programs (and elsewhere)

Abstract: Experiences that are deeply engaging and enjoyable, engender full concentration, and present a balance between challenge and skill promote children's development. This chapter describes a study that sought to identify the kinds of settings and activities that foster engagement and, by extension, positive youth development. The after-school experiences of 191 ethnically diverse youth living in three states, some of whom participated in after-school programs and some of whom did not, were studied. Youth were equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(59 citation statements)
references
References 5 publications
1
57
0
1
Order By: Relevance
“…Perhaps for this reason, youth participation in organized out-of-school activities such as sports, after-school programs, and extracurricular activities have received attention from researchers interested in obesity. These activities tend to limit eating, offer opportunities for physical recreation, and may encourage healthy lifestyles (Mahoney, Lord, & Carryl, 2005a; Vandell et al, 2005). …”
Section: Organized Activity Arrangements During the Summer And Risk Fmentioning
confidence: 99%
“…Perhaps for this reason, youth participation in organized out-of-school activities such as sports, after-school programs, and extracurricular activities have received attention from researchers interested in obesity. These activities tend to limit eating, offer opportunities for physical recreation, and may encourage healthy lifestyles (Mahoney, Lord, & Carryl, 2005a; Vandell et al, 2005). …”
Section: Organized Activity Arrangements During the Summer And Risk Fmentioning
confidence: 99%
“…Another possible explanation may be that the control group condition also consisted of after-school activities, and being engaged in enjoyable activities in their free time at school may have influenced pupils' well-being and their positive engagement with school tasks and school-related activities which, thus, may have led to the lack of differences between the two conditions. In fact, research has shown that after-school activities may contribute to pupils' feeling more intrinsically motivated and to putting more effort into their activities (Fredricks & Simpkins, 2011;Grogan, Henrick, & Malikina, 2014;Vandell et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The initial excitement about participation in T&T set the stage for an engaging experience (Vandell et al, 2005). However, for many, the challenge of working with young children did not provide the right balance of challenge and skill (Larson, 2000) to support building competence and a sense of achievement.…”
Section: Discussionmentioning
confidence: 99%
“…Paired interview 1, School 3 PYD programmes seek to offer an 'engaging experience' (Vandell et al, 2005), that allows for intrinsic motivation, effort and concentration. Engagement is reflected in the extent to which young people are focused and excited about the activities in which they are participating Larson, 2000).…”
Section: Why?mentioning
confidence: 99%